The Responsive Raid: An Analysis of the Dual Logics of Generalization in judging Businesses’ Tax Compliance and in doing Responsive Regulation - Boll, Karen (STS Encounters, 2011)
The article investigates an instance of responsive regulation as a team of inspectors conducts an unannounced raid. The raid takes place in Denmark and its aim is to judge and regulate tax compliance in a number of small businesses. The article argues that different ‘logics of generalization’ is at play as inspectors as well as business owners value the state-of-affairs in the businesses. Furthermore, the article discusses how the inspectors are responsive in the raid. It argues that they are responsive – not primarily towards the behaviour of the taxpayers – but towards a general public. The article hereby engages in the debate concerning what responsive regulation is and how it is played out in practice as the state regulates citizens and businesses. The overall analytical framework is inspired by Helen Verran’s notion of ‘relational empiricism’, and the analysis is an example of how this analytic can be used as a heuristic to analyze ethnographic data.